Historicizing fear : ignorance, vilification, and othering - Boyce, Travis D.; Chunnu, Winsome M. (University Press of Colorado, 2019)
"A historical interrogation from a global perspective of the use of fear to vilify and persecute groups and individuals. Offering a look at racism, fearful framing, oppression, and marginalization, and how 'the Other' is defined and how fear is reinforced, spread, and used for political gain"--